THE AESTHETIC NEEDS OF PATIENTS IN THE DEPARTMENT OF REMOVABLE PROSTHESIS FROM THE CHU-CNOS OF BAMAKO - Ba A.; Koita H.; Kassambara A.; Sogodogo M; Kouyate V.; Thiam A.; Bamba A.; Keita M; Forna Norina Consuela (Romanian Society of Oral Rehabilitation, 2024)
The management of the aesthetic parameter represents an important factor in the integration of removable prostheses. The current major social interest in beauty has made patients more and more demanding with regard to their appearance. [1] The main objective of this study was to assess the aesthetic expectations of patients with removable prostheses at the CHU-CNOS in Bamako. Our prospective and descriptive study having collected 78 patients was carried out over a period from March 2, 2019 to March 9, 2020 at the removable prosthesis department of the CHU-CNOS in Bamako. The female sex represented 55.1% with a sex ratio of 0.65. Removable prosthetic rehabilitation mainly concerned young adults aged 21-41 (41%) Aesthetics was the main reason for rehabilitation most represented with 60.3% of cases. The white tooth was the most requested dental shade with 70.5% of cases Bonded teeth were the most represented in our patients with 71.79% of cases. Pink gum was the shade most requested by our patients with 43.6% of cases. Obtaining a personalized prosthesis in harmony with the facial framework, giving the illusion of naturalness and restoring the smile to patients is the objective to be achieved.